Toxicology of herbal products - Pelkonen, R. O.; Duez, Pierre; Vuorela, Pia Maarit; Vuorela, Heikki (Springer, 2017)
This volume provides a comprehensive overview of the hazards inherent in herbal medicinal products, with systematic coverage of major toxicities. Topics include composition and quality control, toxicokinetics, interactions, safety pharmacology, approaches to studying complex mixtures including metabolomics and systems network pharmacology, and long-term toxicity. The volume also discusses various organ toxicities with a special emphasis on basic mechanisms of actions and the multicomponent and multi-target nature of herbal products. It concludes with a look to future challenges and opportunities. With contributions from noted experts, Toxicology of Herbal Products is a necessary resource for physicians, pharmacists, and toxicologists interested in complex plant-derived products.- Resumé vydavatel
Includes index.
Keywords: léčivé rostliny; toxikologie; medicinal plants; toxicology; elektronické knihy; sborníky; electronic books; papers of several authors